RELATIONSHIP BETWEEN BREAKFAST HABITS AND NUTRITIONAL STATUS WITH THE LEVEL OF LABOR EXHAUSTION AMONG PRODUCTION WORKERS OF PT MARUKI INTERNASIONAL INDONESIA - Michael Satria; Burhanuddin Bahar; Nurhaedar Jafar; Safrullah Amir; Rahayu Indriasari (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Introduction: Work fatigue is a common condition that is experienced by almost all workers, but if this happens continuously it can affect the health condition of workers. Work fatigue can be affected by several factors, some of which are breakfast habits and the nutritional status of workers. Aim: This study aims to determine the relationship between breakfast habits and nutritional status with level of work fatigue of workers in the production division of PT Maruki Internasional Indonesia. Materials and Methods: This research is an analytic observational study using a cross sectional design with a sample of 130 workers from 199 workers in the production division of PT. Maruki Internasional Indonesia was selected using the proportional sampling method. Data collection used a questionnaire for breakfast habits, measurements of body weight and height for nutritional status, as well as an Industrial Fatigue Research Committee (IFRC) questionnaire for work fatigue levels. Data were analyzed using the SPSS application.. Results: The results of the analysis of the associated between breakfast habits and the level of work fatigue, p-value=0.000 (p<0,05), while the results of the analysis of the associated between nutritional status and the level of work fatigue, p-value=0.004 (p<0,05). Conclusion: There is a significant associated between breakfast habits and nutritional status with the level of work fatigue of workers in the production division of PT Maruki Internasional Indonesia. Workers should make it a habit to have breakfast every day before going to work, make the best use of their rest time and maintain their body weight so that their nutritional status remains normal so they can avoid high work fatigue.